Optimizing Resource Allocation in a Cowpea (Vigna unguiculata L. Walp.) Landrace Through Whole-Plant Field Phenotyping and Non-stop Selection to Sustain Increased Genetic Gain Across a Decade - Omirou, Michalis; Ioannides, Ioannis M.; Fasoula, Dionysia A. (Frontiers in Plant Science, 2019)
Cowpea is a warm-season legume, often characterized as an orphan or underutilized crop, with great future potential, particularly under the global change. A traditional cowpea landrace in Cyprus is highly valued for fresh pod consumption in the local cuisine. In order to improve the yield potential of the landrace, the long-term response to direct selection for fresh pod yield and the associated changes in fodder and root biomass were investigated in a variety of fertility regimes under real field conditions. The non-stop selection process employed comprehensive phenotyping at the level of the individual plant and resulted in the creation of a range of highly improved sibling lines with differential adaptation to micro-environments. The average annual genetic gain for fresh pod yield across years is at the level of 30% and seemingly inexhaustible testifying to the great plasticity of the cowpea genome and the potential of the methodology to capture it. Thus, the new focus need not be only on simple variety maintenance, but on the continuous improvement and exploitation of micro-adaptation processes tailored for individual fields. This work presents also a novel approach to the multiple challenges encountered in root phenotyping and a method to meaningfully associate it with whole-plant performance in field conditions.